Adjuvanted recombinant hemagglutinin H7 vaccine to highly pathogenic influenza A(H7N9) elicits high and sustained antibody responses in healthy adults - Oshansky, Christine M.; King, James; Lu, Di; Zhou, James; Pavetto, Corrina; Horwith, Gary; Biscardi, Karen; Nguyen, Bai; Treanor, John J.; Chen, Li-Mei; Jepson, Brett; Bright, Rick A.; et al. (npj vaccines, 2021)
An unprecedented number of human infections with avian influenza A(H7N9) in the fifth epidemic wave during the winter of 2016–2017 in China and their antigenic divergence from the viruses that emerged in 2013 prompted development of updated vaccines for pandemic preparedness. We report on the findings of a clinical study in healthy adults designed to evaluate the safety and immunogenicity of three dose levels of recombinant influenza vaccine derived from highly pathogenic A/Guangdong/17SF003/2016 (H7N9) virus adjuvanted with AS03 or MF59 oil-in water emulsions. Most of the six study groups meet the FDA CBER-specified vaccine licensure criterion of 70% seroprotection rate (SPR) for hemagglutination inhibition antibodies to the homologous virus. A substantial proportion of subjects show high cross-reactivity to antigenically distinct heterologous A(H7N9) viruses from the first epidemic wave of 2013. These results provide critical information to develop a pandemic response strategy and support regulatory requirements for vaccination under Emergency Use Authorization.